(untitled) (Педагогіка вищої та середньої школи, 2008)
In this article the author investigates the problem of primary classes teacher professionally important qualities in the context of subjective approach. Suggested structure of professionally important qualities in theoretically proved and the importance of personal qualities of a teacher as professionally important is mentioned. The author also distinguishes the criteria and significant of professionally important qualities.